Where’s the Carbon: Exploring the Spatial Heterogeneity of Sedimentary Carbon in Mid-Latitude Fjords - Smeaton, Craig; Austin, William E. N. (Frontiers in Earth Science, 2019)
Fjords are recognized as globally significant hotspots for the burial and long-term storage of marine and terrestrially derived organic carbon (OC). By trapping and locking away OC over geological timescales, fjord sediments provide a potentially important yet largely overlooked climate regulation service. Currently, our understanding of the spatial distribution of OC within the surficial sediments of fjords is limited and this potentially implies an overestimation in the global estimates of OC buried in fjords as current calculation methods assume a homogeneous seabed. Using the mid-latitude fjords of Scotland and Ireland as a natural laboratory, we have developed a multi-tiered methodological approach utilizing a spectrum of data ranging from freely available chart data to the latest multibeam geophysics to determine and map the seabed sediment type. Targeted sampling of fjord sediments was undertaken to establish a calibration of sediment type against OC content. The results show that fjord sediments are highly heterogeneous both in sediment type and OC content. Utilizing the tiered mapping outputs, first order estimates of the surficial (top 10 cm) sediment OC stock within Scottish fjords (4.16 ± 0.5 Mt OC) and Irish systems (2.09 ± 0.26 Mt OC), when normalized for area the surficial sediments of Scottish and Irish fjords hold 2027 ± 367 and 1844 ± 94 respectively far exceed estimates for the continental shelf, again highlighting fjord sediments as hotspots for the capture of OC. This tiered approach to mapping sediment type is ideally suited to areas of the marine environment where data availability and quality is a limiting issue. Further understanding of the spatial heterogeneity of these sediments provides a foundation to reevaluate global fjord OC burial rates and to better understand the role of fjord sediments in regulating the global climate.